Maxim of Cooperative Principle Violation by Dodit Mulyanto in Stand-up Comedy Indonesia Season 4 - Satria Raharja, Ahmad Ulliyadhi; Rosyidha, Alfin (State institute of islamic studies salatiga, 2019)
This study focuses on cooperative principle violation done by Dodit Mulyanto in Stand Up Comedy Indonesia season 4 using Grice’s theory. Grice expressed cooperative principle to suggest that in conversational interaction people work on the assumption that a certain set of rules is in operation, unless they receive indications to the contrary. The aims of this research are to classify the maxims of cooperative principle and to explain how Dodit Mulyanto violates cooperative principle to raise humor in Stand Up Comedy Indonesia season 4. Besides, this research is also directed to discover the types of violation maxims, the most dominant violation maxim, and to explain the causes of the most dominant violation maxim in Dodit Mulyanto’s Stand Up Comedy Indonesia season 4. This research is conducted using qualitative method. The sources of data are the 17 videos of Dodit Mulyanto’s speech during his performance in Stand Up Comedy Indonesia Kompas TV season 4 by downloading from YouTube site. The data are the utterances of Dodit Mulyanto which considered contain the violation of cooperative principles. The data are collected using the check list instrument and then analyzed based on the violation on each maxim. At the end, the researcher draws the conclusion which is in accordance with the research finding. The results of the analysis shows that all types of maxim were violated; 12 utterances violation maxim of quantity (24,4%), 13 utterances violation maxim of quality (26,5%), 22 utterances violation maxim of relation (44,9%), and 2 utterances violation maxim of manner (4,1%). The most dominant type of violation maxims was the violation maxim of relation because Dodit Mulyanto delivered too much message, which is unmatched with the topic or changed conversation topic abruptly or did the wrong causality, than is required to raise humor in Stand Up Comedy Indonesia Kompas TV season 4.Keywords: Cooperative Principle, Maxim Violation, Stand Up Comedy.